Molecular dynamics simulations of interfacial properties of shale oil-CO2， CH4， N2 mixtures - ZHOU Yu; SUN Qian; ZHANG Na; LIU Wei; GUO Lingkong; TANG Zhihao; FU Shuoran (Youqi dizhi yu caishoulu)
Oil-gas interfacial tension is an important parameter for analyzing the mixing degree of oil and gas phases and influencing the minimum mixing pressure of oil and gas and the development effect of gas injection during gas flooding for enhanced oil recovery. Aiming at n-octane （C8）， which is the main component of shale oil， the changing rules of interfacial tension and interfacial microscopic characteristics of pure CO2 and mixed gases （CO2， CH4， N2） with n-octane were investigated by molecular dynamics simulation. Additionally， the effects of external factors such as temperature， pressure， and gas components on interfacial characteristics were also taken into account. The results show that with the increase in gas-phase pressure， the mixing degree of gas and n-octane increases， and the microscopic features such as interfacial thickness， roughness， and relative adsorption are enhanced， resulting in a gradual decrease in the interfacial tension between the oil and gas. The interfacial tension shows opposite trends with temperature in different pressure intervals. The interfacial tension declines as the temperature rises in low pressure intervals. While the interfacial tension grows as the temperature rises in high pressure intervals. Compared with pure CO2， the addition of CH4 and N2 increases the interfacial tension between the mixed gases and the oil， of which N2 has a greater effect on the oil-gas interfacial tension. At the same time， CH4 and N2 weaken the microscopic features such as the oil-gas interfacial thickness and relative adsorption. The relative adsorption of CO2 is the largest， followed by CH4 and the smallest N2 in the ternary CO2+CH4+N2/C8 system， which proves that the interactions between the three gases and the oil are from the strong to the weak， i.e.， CO2CH4N2. In addition， the relative adsorption of all the systems is greater than zero. As the adsorption is larger， the interfacial tension decreases faster with the increasing pressure， which is in agreement with Gibbs’ adsorption theory.